2017
DOI: 10.18388/abp.2017_1565
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrazine derivatives of 3-formylchromones on angiogenic basic fibroblast growth factor and fibroblast growth factor receptor-1 in human melanoma cell line WM-115

Abstract: The hydrazine derivatives of benzopyrones remain an unexplored group of chemical compounds. This preliminary study investigates the influence of A-5, CH-3 and K-2 derivatives at concentrations of 1, 10, 100 nM and 1 μM on selected biochemical factors of a melanoma cell line WM-115, with regard to their potential angiogenic properties. The studied compounds were found to influence cell proliferation, as well as total protein, bFGF and FGFR1 concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…Previous studies have confirmed the antiproliferative properties [ 12 , 31 ] and biochemical activity [ 32 , 33 ] of 3-formylchromone derivatives. Moreover, biological activity of copper (II) complexes of 3-formylchromone, was also described [ 21 ]; however, hydrazine and hydrazide derivatives of benzopyrones with fluorine substituents remain a poorly-analyzed group of compounds.…”
Section: Introductionmentioning
confidence: 66%
“…Previous studies have confirmed the antiproliferative properties [ 12 , 31 ] and biochemical activity [ 32 , 33 ] of 3-formylchromone derivatives. Moreover, biological activity of copper (II) complexes of 3-formylchromone, was also described [ 21 ]; however, hydrazine and hydrazide derivatives of benzopyrones with fluorine substituents remain a poorly-analyzed group of compounds.…”
Section: Introductionmentioning
confidence: 66%
“…Ну и наконец, мы нашли подтверждения, пусть и крайне немногочисленные, тому, что ксенобиотики также способны индуцировать стволовость опухолевых клеток [113,114], а также активировать экспрессию 21 из 96 «генов стволовости» TAMRA+ клеток опухоли Кребс-2: Abca1 [115], Acpp [81], Aldh1a1 [42], Cp [116], Cyp7a1 [117], Fgfr1 [118], Gas6 [119], Gstm3 [120], Igf1 [121], Igf2 [122], Il10 [123,124], Mmp2 [125], Nrcam [126], Pde4d [127], Pdk4 [128], Per2 [129], Pf4 [130], Pon1 [131], Rragd [105], Serpinb2 [132], Wnt5a [133].…”
Section: индукция «генов стволовости» в условиях генерализованного клunclassified